Combination of rehydrated whey protein isolate aqueous solution with blackcurrant concentrate and the formation of encapsulates via spray-drying and freeze-drying: Alterations to the functional properties of protein and their anticancer properties. (1st September 2021) - Wu, Gang; Hui, Xiaodan; Liang, Jiaxi; Liu, Huifan; Chen, Han; Gong, Xi; Brennan, Margaret A.; Zeng, Xin-An; Guo, Xinbo; Brennan, Charles S.
Highlights: Both spray- and freeze-drying treatments altered whey protein functional properties. Whey protein functional properties has been modified by blackcurrant concentrate. Blackcurrant concentrate fortified whey protein with anticancer properties. Individual whey component interacts with blackcurrant anthocyanins differently. Abstract: Novel protein ingredients were produced by encapsulating blackcurrant concentrate (BC) with whey protein through spray-, or freeze-, drying strategies. The effects of encapsulation strategies and the addition of BC on the physical and functional characteristics, and anticancer activity of the ingredients were evaluated. The mechanistic interactions between the blackcurrant anthocyanins (BAs) with the whey protein components were predicted via in silico studies. HPLC results revealed that spray-dried and freeze-dried whey protein-BC encapsulates have effectively delivered the BAs. The physical and functional properties of the proteins were altered by drying strategies and the addition of BC. Anticancer effects were linked to reactive oxygen species production and cell apoptosis towards HepG2. Molecular docking results showed that hydrogen bonds were the main binding forces between BAs and various whey protein molecules, resulting in the formation of complexes. These findings are relevant to the formulation of powdered products to be used as ingredients in practical food matrix.